2020
DOI: 10.3390/genes12010059
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 Induced Somatic Recombination at the CRTISO Locus in Tomato

Abstract: Homologous recombination (HR) in somatic cells is not as well understood as meiotic recombination and is thought to be rare. In a previous study, we showed that Inter-Homologous Somatic Recombination (IHSR) can be achieved by targeted induction of DNA double-strand breaks (DSBs). Here, we designed a novel IHSR assay to investigate this phenomenon in greater depth. We utilized F1 hybrids from divergent parental lines, each with a different mutation at the Carotenoid isomerase (CRTISO) locus. IHSR events, namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 23 publications
2
20
1
Order By: Relevance
“…The length of conversion tracts was variable, ranging from 5 pb to 7505 bp, with short and simple conversion tracts or longer and more complex tracts (Figure 2). The phenomena of a long and complex conversion tract (also known as an interrupted or discontinued gene conversion tract) was also observed in our previous work on tomato Psy1 [23] and CRTISO [44] and was also shown for both somatic and meiotic repair of yeast [45,46] and mammalian cells [47,48]. Complex conversion tracts were shown to be the result of the mismatch repair mechanism in heterozygous heteroduplexes of D-loop in SDSA or double Holliday Junctions intermediates [49][50][51][52].…”
Section: Conversion Tract Patternssupporting
confidence: 68%
See 1 more Smart Citation
“…The length of conversion tracts was variable, ranging from 5 pb to 7505 bp, with short and simple conversion tracts or longer and more complex tracts (Figure 2). The phenomena of a long and complex conversion tract (also known as an interrupted or discontinued gene conversion tract) was also observed in our previous work on tomato Psy1 [23] and CRTISO [44] and was also shown for both somatic and meiotic repair of yeast [45,46] and mammalian cells [47,48]. Complex conversion tracts were shown to be the result of the mismatch repair mechanism in heterozygous heteroduplexes of D-loop in SDSA or double Holliday Junctions intermediates [49][50][51][52].…”
Section: Conversion Tract Patternssupporting
confidence: 68%
“…Previous studies have used transgenic markers to analyze DSB-induced somatic intrachromosomal HR based repair [41,42], inter-chromatid unequal crossover [21], or inter-homolog recombination in plants [43]. In recent works [23,44], we demonstrated that DSB repair can also occur via HR between homologous chromosomes in somatic cells at a single endogenous locus, the Psy1 and the CRTISO genes in tomato. Here, we extended the study of targeted IHR to several targets in Arabidopsis thaliana, in various epigenetic contexts such as euchromatin, heterochromatin islands embedded within euchromatin to heterochromatin located at pericentric loci.…”
Section: Discussionmentioning
confidence: 90%
“…The extremely short conversion tracts found here differ from previous observations in humans and plants [ 16 , 19 , 20 , 21 ]. Differences in cell state between studies (here non-dividing cells and non-selected compared to actively dividing cells with GT-specific selection) may at least partially explain conversion tract length differences, as homologous recombination is tightly regulated by the cell cycle [ 22 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, in mammals, loss of heterozygosity, which can be induced by large deletions, somaclonal recombination and gene conversion between homologous chromosomes occur in somatic cells. It has been shown that site‐specific Cas9‐mediated induction of DNA DSBs induced targeted gene conversion and crossover events in tomato (Ben Shlush et al, 2021; Filler Hayut et al, 2017), suggesting the additional possibility of targeted recombination between homologous chromosomes in somatic cells of plants without reproduction processes. Targeted recombination in somatic cells would be a breeding tool to produce near‐isogenic lines in a shorter period.…”
Section: Chromosome and Genome Rearrangementmentioning
confidence: 99%